Preparation of palladium, palladium sulfide, cadmium selenide nanoparticles and magnesium oxychloride, magnesium hydroxide nanorods - Yang, Zhiqiang (Kansas State University, 2008)
First, a new tiara Pd(II) thiolate complex-[Pd(SC[subscript]12H[subscript]25)[subscript]2][subscript]6 has been synthesized and fully characterized. Then the complex was further used as a single-source precursor to prepare nearly monodisperse palladium sulfide (PdS) nanoparticles through the high-temperature-induced decomposition in diphenyl ether. Secondly, the influence of dodecanethiol on the product distribution upon heating a Pd(II)-octylamine system was investigated. The molar ratio of octylamine to Pd(II) was fixed at 20:1, and the concentration of dodecanethiol was changed systematically. Without thiol ligand, only aggregated Pd(0) particles were obtained due to the reduction of Pd(II) by octylamine. When the molar ratio of dodecanethiol to Pd(II) was increased to 0.5, highly monodisperse sulfurized palladium nanoparticles with diameter 7.55 [plus or minus] 0.73 nm were generated. When the molar ratio reached to 2, only a thiolate complex-[Pd(SC[subscript]12H[subscript]25)[subscript]2][subscript]6 was found as the final product. Thirdly, we report a facile method to prepare nearly monodisperse Pd nanoparticles by heating Pd(II) ions in 4-tert-butyltoluene solvent, in the presence of oleylamine and trioctylphosphine (TOP) ligands. It has been found the concentration of TOP ligand was highly pivotal for the formation of Pd nanoparticles. Without TOP, only aggregated Pd particles were obtained due to the reduction of Pd(II) by oleylamine. When the molar ratio of TOP to Pd(II) was less than two, well-protected Pd nanoparticles were obtained. However, when the molar ratio reached to two, only Pd(II)-TOP coordination complexes were obtained as the final product. Fourthly, we present a novel way to synthesize cadmium selenide (CdSe) nanoparticles from a heterogeneous system only containing cadmium oxide, trioctylphosphine, and trioctylphosphine selenide. Last, the formation of magnesium oxychloride (Mg[subscript]x(OH)[subscript]yCl[subscript]z•nH[subscript]2O) nanorods from the system MgO-MgCl[subscript]2-H[subscript]2O was investigated. By changing the amounts of the starting materials, short nanorods (< 1 micron) or long nanorods (up to 20 micron) could be obtained readily with the aspect ratio in the range of 10-70. The resulting magnesium oxychloride nanorods could be further transformed to magnesium hydroxide (Mg(OH)[subscript]2) nanorods by treating with NaOH.
Keywords: palladium; nanoparticles; palladium sulfide; nanorods; magnesium hydroxide; CdSe; Chemistry, Inorganic (0488)